2019
DOI: 10.1177/1120672119887874
|View full text |Cite
|
Sign up to set email alerts
|

Corneal collagen cross-linking with and without simultaneous intrastromal corneal ring segment implantation: One-year pilot study

Abstract: Aim: The aim of this study was to assess and compare the visual, refractive, and topographic outcomes of keratoconic eyes treated with corneal collagen cross-linking combined with and without same day intrastromal corneal ring segment over the first 12 months. Methods: This prospective randomized study analyzed 38 eyes of 30 consecutive keratoconus patients aged 26.21 ± 6.97 (range = 15–41) years. A total of 20 eyes were treated with collagen cross-linking alone, and 18 eyes underwent collagen cross-linking co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Coshkunseven et al reported an efficacy and safety of combined treatment, including posterior chamber toric phakic Visian ICL implantation after Keraring ICRS implantation followed by CXL in a three-step procedure in 14 keratoconic eyes with extreme myopia and astigmatism [ 16 ]. These works present mainly the results of combined treatment and there are just a few studies comparing the efficacy of various types of combined treatment [ 7 , 23 ]. Hosny et al presented the comparative results of two variations of combined surgical treatment in keratoconus, including different CXL types: a combination of intra-tunnel CXL with ICRS implantation and a combination of epithelium-off CXL with ICRS in 20 eyes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coshkunseven et al reported an efficacy and safety of combined treatment, including posterior chamber toric phakic Visian ICL implantation after Keraring ICRS implantation followed by CXL in a three-step procedure in 14 keratoconic eyes with extreme myopia and astigmatism [ 16 ]. These works present mainly the results of combined treatment and there are just a few studies comparing the efficacy of various types of combined treatment [ 7 , 23 ]. Hosny et al presented the comparative results of two variations of combined surgical treatment in keratoconus, including different CXL types: a combination of intra-tunnel CXL with ICRS implantation and a combination of epithelium-off CXL with ICRS in 20 eyes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the strengths of our study is that we compared not only the results of a combined keratoconus treatment method (CXL and ICRS) with non-combined options [ 1 , 5 , 7 , 12 ], but also different types of two-stage surgical treatment of keratoconus with the use of transepithelial TG-PRK. CXL and ICRS, as well as a combined version (CXL+ICRS) followed by TG-PRK are more clinically effective than methods without use of TG-PRK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prospective study suggested that CXL with simultaneous ICRS implantation gives an additional improvement in UDVA with significant reduction in cylinder and spherical equivalent. 24 Debate still exists as to which procedure should be performed first, with an additional option of performing the procedures simultaneously. A 2018 meta-analysis reviewing best corrected visual acuity (BCVA) and uncorrected visual acuity (UCVA) outcomes for those patients undergoing subsequent (CXL then ICRS) versus simultaneous procedures found superior refractive outcomes in the patient group undergoing simultaneous procedure.…”
Section: Combined Intracorneal Ring Segments and Corneal Crosslinkingmentioning
confidence: 99%